2012
DOI: 10.1038/ejcn.2012.180
|View full text |Cite
|
Sign up to set email alerts
|

Red and processed meat consumption and risk of stroke: a meta-analysis of prospective cohort studies

Abstract: Findings from this meta-analysis indicate that consumption of red and/or processed meat increase risk of stroke, in particular, ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 33 publications
2
103
2
3
Order By: Relevance
“…33,34 Relative to that, climate change leads to changes in temperature and precipitation, which is expected to reduce global crop productivity, 5,15 and via market responses, lead to changes in management intensity, cropping area, consumption, and international trade. 6 From a health perspective, changes in food availability and consumption affect dietary and weigh-related risk factors associated with an increased incidence of non-communicable diseases and mortality, such as low fruit and vegetable consumption, [16][17][18] high red meat consumption, [18][19][20] and increased body weight. 21,22 In line with the conceptual framework, we devised a multi-step methodology, depicted in Figure 1, which leads from climate-change impacts on agricultural yields, through changes in food production and consumption, to changes in dietary and weight-related risk factors and associated mortalities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Relative to that, climate change leads to changes in temperature and precipitation, which is expected to reduce global crop productivity, 5,15 and via market responses, lead to changes in management intensity, cropping area, consumption, and international trade. 6 From a health perspective, changes in food availability and consumption affect dietary and weigh-related risk factors associated with an increased incidence of non-communicable diseases and mortality, such as low fruit and vegetable consumption, [16][17][18] high red meat consumption, [18][19][20] and increased body weight. 21,22 In line with the conceptual framework, we devised a multi-step methodology, depicted in Figure 1, which leads from climate-change impacts on agricultural yields, through changes in food production and consumption, to changes in dietary and weight-related risk factors and associated mortalities.…”
Section: Methodsmentioning
confidence: 99%
“…The diet and weight-related relative risk parameters were adopted from pooled analyses of prospective cohort studies, 21,22 and from meta-analysis of prospective cohort and case-control studies. 19,20,[16][17][18] The cancer associations have been judged as probable or convincing by the World Cancer Research Fund, and in each case a dose-response relationship was apparent and consistent evidence suggests plausible mechanisms. 18 …”
Section: Health Modelling Frameworkmentioning
confidence: 99%
“…Population and mortality projections for the year 2050 were adapted from the United Nations Population Division and the World Health Organization (WHO), respectively. The diet and weight-related relative risk parameters (SI Appendix, Table S4) were taken from pooled analyses of prospective cohort studies (18,19) and from metaanalyses of prospective cohort and case-control studies (28,(41)(42)(43)(44)(45)(46). The cancer associations have been judged as probable or convincing by the World Cancer Research Fund, and, in each case, a dose-response relationship had been identified and there was consistent evidence suggesting a plausible mechanism (28).…”
Section: Methodsmentioning
confidence: 99%
“…In general, plant proteins have been related to health benefits more than animal proteins (14)(15)(16)(17) . While vegetable protein intakes have been found to be inversely associated with blood pressure (18) , a high consumption of red and/or processed meat has been associated with a number of adverse cardiovascular health outcomes such as higher systolic blood pressure (19) , increased risk for type 2 diabetes (20)(21)(22) , ischaemic stroke (23) , global and central obesity (24,25) and weight gain (26,27) .…”
mentioning
confidence: 99%